Analisis Faktor Sosial Ekonomi yang Mempengaruhi Curahan Jam Kerja Wanita Tani Padi Sawah Di Desa Haekto Kabupaten Timor Tengah Utara - Maria F. Selan; Adeline N. Hutapea (Fakultas Pertanian, Universitas Timor, 2019)
that affect the outpouring of farm woman working hours in paddy’s farming in Haekto Village. The method used is descriptive analysis and quantitative analysis using multiple linear regression. This research was conducted in January-September 2018 in Haekto Village. The sampling technique in this study was a simple random sampling technique and was determined using the Slovin formula so that the number of respondents was 58 person. The results of the analysis show that the factors that influence the outpouring of farm woman working hours in Haekto Village are significantly land area and age. The other independent variables in this study did not have a significant effect on the outpouring of working hours of women paddy’s farmer in Haekto Village.